Communicating ingredient authenticity in product packaging for luxury Korean cosmetics - the case of ginseng and snail mucus - Lee, Sean (2015)
The recent success of luxury Korean cosmetic products have caught the attention of researchers around the world. Products using authentic Korean ginseng and snail mucus are seeing unprecedented growth in recent years. The current study will explore the effects country image and authenticity of packaging have on consumer attitude and behavioural intention. This study will employ a 2x2 between-subjects experimental design to test the effects of indexical and iconic authentic package designs on consumer perceptions. The study contributes to the research area by integrating the authenticity literature and extending authenticity’s applicability to the packaging of Luxury Korean Cosmetics industry.